Are we approaching the development of a novel calcium phosphate-based bioceramic dental material? - Pereira, Letícia Florindo; de Azevedo-Silva, Lucas José; Minim, Pedro Rodrigues; Lisboa-Filho, Paulo Noronha [UNESP]; Fortulan, Carlos Alberto; Griggs, Jason Alan; Ferrairo, Brunna Mota; Borges, Ana Flávia Sanches (Elsevier, 2024)
Objectives: Develop a sustainable bovine hydroxyapatite dental ceramic with the addition of titanium dioxide (TiO2) nanoparticles (5 % and 8 % by weight), analyzing the outcome of this addition to the microstructure, as well as its mechanical and chemical properties, in order to evaluate whether they satisfy the International Organization for Standardization (ISO) 6872:2015 for dental ceramics or not. Methods: Disks were obtained through uniaxial followed by isostatic pressing from bovine hydroxyapatite powder and TiO2 nanoparticles and sintered at 1300ºC for 2 h. Three experimental groups were developed (HA, HA+5 %TiO2 and HA+8 %TiO2) and subjected to X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), indentation fracture (IF), biaxial flexural strength (BFS) and chemical solubility test. Results: XRD revealed, for HA group, the appearance of a peak corresponding to b-tricalcium phosphate (ß-TCP). For HA+ 5 %TiO2 and HA+ 8 %TiO2, the entire composition was converted into ß-TCP and calcium titanate (CaTiO3). The SEM images showed a dense ceramic matrix and a uniform distribution of another phase in groups with TiO2 nanoparticles. HA+ 5 %TiO2 (1.40 ± 0.18 MPa.m1/2) and HA+ 8 %TiO2 (1.32 ± 0.18 MPa.m1/2) showed significantly higher fracture toughness values than HA (0.67 ± 0.09 MPa.m1/2). HA showed significantly higher characteristic stress (295.8 MPa) in comparison to groups with 5 % (235.1 MPa) and 8 % (214.4 MPa) TiO2 nanoparticles. Differences were not observed between the Weibull modulus values. The solubility results indicated that all experimental ceramics were above the 2000 ug/cm2 limit set by the ISO 6872:2015. Significance: This study proposed the development and characterization of a new ceramic for dental prosthesis made from HA extracted from bovine bones, with the intention of reusing these solids waste and transforming them into a sustainable and low-cost material. Although the experimental calcium phosphate ceramic with additions of 5 % and 8 % of TiO2 achieved desirable mechanical properties, the chemical solubility values were very high.
Keywords: Apatites; Ceramics; Dental materials; Nanotechnology